Low cost house quality developed by Permodalan Negeri Selangor Berhad / Sumayyah Shaidan - Shaidan, Sumayyah (Faculty of Business and Management, 2006)
The Malaysian government started building low cost housing during its first five-year plan from 1956 to 1960. The objective of building the low cost houses was to promote welfare of the lower income groups by providing• improved and decent houses, and enhancing social and community services. Malaysian government has given the responsibilities to all state government to build low cost houses in order to promote welfare of lower income group. After that, state government will give the responsibilities to the developer to develop low cost houses. State government of Selangor, has given the responsibilities to the Permodalan Negeri Selangor Berhad to develop low cost houses in order to promote lower income groups of Selangor residents.